2022
DOI: 10.1111/jog.15233
|View full text |Cite
|
Sign up to set email alerts
|

Updated meta‐analysis on the diagnostic accuracy of serum anti‐Mullerian hormone in poly cystic ovary syndrome involving 13 509 subjects

Abstract: Aim: To determine the diagnostic accuracy of anti-Mullerian hormone (AMH) in the diagnosis of polycystic ovary syndrome (PCOS). Methods: Two independent reviewers searched the electronic databases and search engines using PubMed, Cochrane library, and Google Scholar systematically to retrieve relevant articles published from inception to September 2021. The diagnostic efficacy of AMH was computed using the random-effects model in terms of pooled sensitivity, specificity, and diagnostic odds ratio (DOR) with 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
0
6
0
2
Order By: Relevance
“…57 Two other meta-analyses demonstrated the usefulness of AMH levels in diagnosing PCOS, regardless of age. 56,59 Although the cut-off value for AMH was set at 4.7 ng/mL, in the meta-analysis of In this regard, a meta-analysis of exclusively adolescents with PCOS has shown the usefulness of AMH measurement for diagnosing PCOS, and that the cut-off value is approximately 6-7 ng/mL. 55 PCOS is a syndrome with several different diagnostic criteria, of which polycystic ovary morphology (PCOM) is one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Two other meta-analyses demonstrated the usefulness of AMH levels in diagnosing PCOS, regardless of age. 56,59 Although the cut-off value for AMH was set at 4.7 ng/mL, in the meta-analysis of In this regard, a meta-analysis of exclusively adolescents with PCOS has shown the usefulness of AMH measurement for diagnosing PCOS, and that the cut-off value is approximately 6-7 ng/mL. 55 PCOS is a syndrome with several different diagnostic criteria, of which polycystic ovary morphology (PCOM) is one.…”
Section: Resultsmentioning
confidence: 99%
“…A 2021 meta‐analysis demonstrated that the mean difference in AMH levels between the PCOS and control groups was 0.97 (0.60–1.34) ng/mL 57 . Two other meta‐analyses demonstrated the usefulness of AMH levels in diagnosing PCOS, regardless of age 56,59 . Although the cut‐off value for AMH was set at 4.7 ng/mL, in the meta‐analysis of individual participant data, 59 the cut‐off values were widely distributed in the recruited studies.…”
Section: Resultsmentioning
confidence: 99%
“…Le taux d’hormones antimüllériennes est aussi un marqueur du nombre de follicules. Une méta-analyse récente laisse entendre qu’un seuil de diagnostic approprié pour le de SOPK serait un taux d’hormones antimüllériennes de 34,2 pmol/L 15 . Les valeurs et les seuils dépendent étroitement de l’âge et des résultats d’analyses 1 .…”
Section: Comment Diagnostique-t-on Le Sopk?unclassified
“…Anti-Müllerian hormone (AMH) is a regulator of follicle recruitment from the primordial follicle pool and inhibitor of follicular growth that is expressed by granulosa cells in the preantral and small antral follicles [23,24]. Serum AMH levels correlate well with the 2-9 mm antral follicles found in TVUS examination in the diagnosis of PCOM [25,26]. Elevated levels of AMH are observed in women with PCOS [27][28][29][30], and a strong correlation between elevated levels of AMH and increased AFCs has been demonstrated [12,14,26,29], supporting the use of AMH as a biomarker for PCOM.…”
Section: Introductionmentioning
confidence: 99%
“…Serum AMH levels correlate well with the 2-9 mm antral follicles found in TVUS examination in the diagnosis of PCOM [ 25 , 26 ]. Elevated levels of AMH are observed in women with PCOS [ 27 - 30 ], and a strong correlation between elevated levels of AMH and increased AFCs has been demonstrated [ 12 , 14 , 26 , 29 ], supporting the use of AMH as a biomarker for PCOM.…”
Section: Introductionmentioning
confidence: 99%